Effects of the insecticide flupyradifurone and the fungicides pyraclostrobin and fluxapyroxad on behavior and morphophysiology in Melipona scutellaris - Inoue, Lais Vieira Bello [UNESP]; da Costa Domingues, Caio Eduardo; Lancia, Beatriz Carvalho [UNESP]; Nocelli, Roberta Cornélio Ferreira; Malaspina, Osmar [UNESP] (Elsevier, 2025)
Native stingless bees are important for natural ecosystems and human nutrition. However, they may be exposed to pesticides used in agriculture. Pesticides are sold as commercial formulations, either with a single active ingredient (e.g., flupyradifurone insecticide) or multiple ones (e.g., pyraclostrobin and fluxapyroxad fungicide). Considering the impact of pesticides on non-target organisms, this study aimed to evaluate the effects of these isolated and combined formulated products on the survival, behavior, and morphophysiology of the midgut and Malpighian tubules of Melipona scutellaris foragers. Sampled bees were divided into the following experimental groups: insecticide (6 ng/μL of flupyradifurone), fungicide (0.1 ng/μL of pyraclostrobin and 0.05 ng/μL of fluxapyroxad), and a combination of both solutions (flupyradifurone: 3 ng/μL, pyraclostrobin: 0.05 ng/μL, and fluxapyroxad: 0.025 ng/μL). Individuals were chronically exposed to pesticides orally to record the survival probability. According to the result, a new bioassay was performed to evaluate their behavior and organ lesion indexes. Exposed bees exhibited high mortality compared to the control experimental group. The insecticide group showed significant alterations in mobility over the course of the experiment, and all experimental groups demonstrated impaired behavior. Histological images also revealed the presence of three levels of injury in the midgut (cell elimination, apocrine secretion, spherocrystals, vacuolization and pycnotic nuclei) and Malpighian tubules (spherocrystals, vacuolization and pycnotic nuclei) following a brief exposure period. The data demonstrate that, even in the short term, both formulated products impair the health and survival of the species, disrupting the internal dynamics of the colony and consequently lead to its weakening.
Keywords: Behavioral assays; Commercial pesticide formulations; Ecotoxicology; Malpighian tubules; Meliponini; Midgut